If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17y + 60 = 9 Reorder the terms: 60 + 17y = 9 Solving 60 + 17y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 17y = 9 + -60 Combine like terms: 60 + -60 = 0 0 + 17y = 9 + -60 17y = 9 + -60 Combine like terms: 9 + -60 = -51 17y = -51 Divide each side by '17'. y = -3 Simplifying y = -3
| 4(4a+9)+6= | | 5time-29=6 | | -47-6x+x=84 | | F(x)=x^2+x+.25 | | x(-4)=265 | | 3x^2+5x=291 | | -4(9z-8)= | | 4-(x+14)=3x-2 | | n/20=20 | | 8(c+2)= | | (x+1)(x+1)=-19 | | 10x^4-9x^2y-9y^2=0 | | X=-3/2y^2 | | b/3=27 | | -7x-y=23 | | 6/7÷2 | | x^2-50x+125=0 | | 4x-7=16-69 | | 9x+3-8x+8=24 | | n/16=1 | | -4x+3=-7x+15 | | y=2sin(4x)+3 | | 4x+3x=13+19 | | -7(6k-4)-7k= | | 88000+20x=30x | | (6x^2+7x-5)-(3x^2+2x-7)= | | 0=4x^3+2x-5 | | 5(3w)= | | 5x+x=4x-7 | | -12+7x^2=0 | | 14a-13=11a+2 | | 10x-20=-20x |